Assessment of photometric and electrical measurements of residential light sources - Dogansahin, Kadir; Ayaz, Ramazan; Bozkurt, Altug; Kekezoglu, Bedri (SPRINGER, 2021)
The development of light sources that provides lighting with electrical energy has a history of about 200 years and it has still been continuing today. Over the time, different light sources have been developed by the use of different technologies. Eventually, a large product inventory comprised from light sources in different structures and characteristics has been obtained. Residential lighting is an important field in the sector in terms of appealing large number of users and a wide range of application areas. In addition, lighting quality is prioritized in residential buildings, because people get more closely exposed to artificial light in those places. In this study, the most commonly used eight different light sources in residential buildings have been investigated. The selected light sources are comprised of the products from halogen, CFL and LED lighting technologies. All the light sources have been chosen with equivalent luminous flux values. The selected light sources have been subjected to photometric and electrical measurements realized simultaneously under the same ambient conditions. The interactions between photometric parameters and the meaning of these magnitudes in terms of users have been tried to be explained in an explanatory language. For the same purpose, electrical parameters have been also examined and their meanings terms of both the user and system have been given. Based on the results obtained, evaluation of the light sources selected from different technologies have been provided sophisticatedly and their suitability in terms of users and systems have been discussed. In the last part, the loading efficacy value has been examined and reference has been made to the appropriateness of the use of this value in expressing the efficiency of the light sources.
Keywords: Compact fluorescent lamps; Electrical light sources; Light emitting diodes; Photometry; Power quality; Engineering